TIMP3 induces gene expression partly through PI3K and their association with vascularization and heart rate - Xia, Zi-Meng; Song, Meng-Yu; Chen, Yan-Ling; Cui, Guozhen; Fan, Dong (Frontiers in Cardiovascular Medicine, 2023)
Background: Tissue inhibitor of metalloproteinase 3 (TIMP3) was recently demonstrated capable to regulate some gene expression in a myocardial infarction model. Here we aim to explore the gene expression profile in TIMP3-treated cardiomyocytes and related potential cardiovascular functions. Methods: Total RNA extracted from cultured neonatal rat ventricular myocytes (NRVMs) were used for RNA sequencing analysis and real-time PCR. KEGG pathway enrichment assay and Ingenuity Pathway Analysis (IPA) were performed to study the signaling pathways and downstream effects. Western blot was used to detect phosphorylation of protein kinase B (Akt). A Cell Counting Kit-8 assay was employed to evaluate the proliferation of human umbilical vein endothelial cells (HUVECs). Contraction rate of NRVMs was measured with microscopy. Results: RNA sequencing data showed that expression of 2526 genes were significantly modulated by recombinant TIMP3 (rTIMP3, 100ng/ml) in NRVMs. Some differentially expressed genes (DEGs) were validated with real-time PCR. Several KEGG pathways including the phosphoinositide-3-kinase (PI3K)-Akt pathway were significantly regulated by rTIMP3. Phosphorylation of Akt was increased by rTIMP3 and a PI3K inhibitor LY294002 suppressed rTIMP3-induced up-regulation of some genes. Some DEGs were predicted by IPA to increase vascularization, and some to decrease heart rate. RTIMP3 could reduce the contraction rate of NRVMs and its conditioned media increased the proliferation of HUVECs. Conclusion: TIMP3 can regulate expression of multiple genes partly through PI3K. Some DEGs were associated with activation of vascularization and some with heart rate reduction. This study suggests that TIMP3 can potentially modulate cardiovascular functions via DEGs.